Multiple Distinct Splicing Enhancers in the Protein-Coding Sequences of a Constitutively Spliced Pre-mRNA - Schaal, Thomas D. (American Society for Microbiology, 1999)
We have identified multiple distinct splicing enhancer elements within protein-coding sequences of the constitutively spliced human β-globin pre-mRNA. Each of these highly conserved sequences is sufficient to activate the splicing of a heterologous enhancer-dependent pre-mRNA. One of these enhancers is activated by and binds to the SR protein SC35, whereas at least two others are activated by the SR protein SF2/ASF. A single base mutation within another enhancer element inactivates the enhancer but does not change the encoded amino acid. Thus, overlapping protein coding and RNA recognition elements may be coselected during evolution. These studies provide the first direct evidence that SR protein-specific splicing enhancers are located within the coding regions of constitutively spliced pre-mRNAs. We propose that these enhancers function as multisite splicing enhancers to specify 3′ splice-site selection.